Lord Murugan in the vedas - Rajantheran, M.; Viknarasah, R. (2014)
The worship of Lord Muruga is not only an ancient religious practice of the Tamils but it is also being a bridge to connect the civilization, culture, beliefs and tradition of them. The Sanggam literature hails Lord Muruga as the Lord of the Kurunji land. But even the Vedas which were written long before the Sang gam literature praise Lord Muruga with special superiority. Among the four Vedas namely Rig, Yajur, Sarna, Aiharoa, Rig Veda is considered to be the oldest. Even in the Rig Veda, there found many pieces of information about Lord Muruga. Lord Muruga is referred to as Agnibhu, Sadasapati, Skanda and Subramanya. What do the names means? What is the significance of Lord Muruga in the Vedas? The article aims at giving a clear insight into all these aspects. In order to prove it with evidence, the Vedic verses and Maha Vakyas of Lord Muruga are also given with their meaning. Furthermore, in order to reinforce the points, research materials found in Ramayana, Bagavath Gita and Upanishads are also incorporated.